Essays on political economy - Silva, Luiz Gustavo Araújo da Cruz Casais e (2022)
This thesis is composed of three essays related to Political Economy. The first two investigate the migratory movement of the beginning of the 21st century to Brazil, its relationship with electoral results, and they share the same database. The third examines the sociopolitical impact of an economic decline in the cacao region in the state of Bahia, Brazil. The first chapter analyzes the impact of the international immigration on the presidential elections in Brazil between 2006 and 2018. For this purpose, it uses two instrumental variables: (i) based on the geographical distance, and (ii) the shift-share. The results suggest that if a municipality hosts the mean of the immigrant share of the local population, the PT’s vote share reduces by 5.25 percentage points (p.p.). For the heterogeneous effect, I find that the impact is stronger for municipalities that (i) host a lower share of immigrants, (ii) have a lower population, (iii) have a higher unemployment rate, and (iv) hold a lower educational quality. Higher immigrant share increases the PT’s vote share in the Brazilian South region. Besides, restricting the estimations for different election cycles, the impact becomes then positive in the 2006–2010 cycle and negative for the remainder. The mechanism analysis suggests that the electoral impact potentially run through the increase of foreign student share in the educational system, which may be a proxy of competition for public goods. Moreover, I find that immigrants reduce homicide, increase municipality spending per capita, and its net revenues. The second chapter examines whether immigrants make decisions about where to go within a country based on the election outcomes. I use the results of the Brazilian mayoral elections of 2004 and 2008 on the number of long-term visa requests at the municipality level. The political variables are three: left and center political parties, PT, and PSDB. The investigation employs the instrumental variable approach to verify he causal effect of the phenomenon. The estimates suggest that a 1 p.p. increase of the left and center parties’ vote share is correlated with the raise of immigration by 0.7 per municipality. The results, though, should not be interpreted as causal, since the robustness checks suggest that the the instrumental variable assumptions are not satisfied. The third chapter assesses the electoral consequences of the economic decline of Brazil’s most productive cocoa region after infection with the witches’ broom disease. I run tworesearch designs, namely, the difference in differences and the instrumental variable. I find evidence that the voters in the affected area punished the incumbent’s presidential candidate in the short-run, by increasing the Workers’ Party vote share. With respect to the gubernatorial election, the results suggest the same movement: the voters punished the incumbent’s party persistently throughout the entire period analyzed by giving a higher share of votes to the Liberal Front Party. Voters are more responsive among the municipalities with the highest GDP per capita, highest cocoa production, and highest rural population. The mechanism analysis reveal that the phenomenon raised the unemployment rate, the poverty, and the inequality.